2017
DOI: 10.3390/bios8010002
|View full text |Cite
|
Sign up to set email alerts
|

An FT-Raman, FT-IR, and Quantum Chemical Investigation of Stanozolol and Oxandrolone

Abstract: We have studied the Fourier Transform Infrared (FT-IR) and the Fourier transform Raman (FT-Raman) spectra of stanozolol and oxandrolone, and we have performed quantum chemical calculations based on the density functional theory (DFT) with a B3LYP/6-31G (d, p) level of theory. The FT-IR and FT-Raman spectra were collected in a solid phase. The consistency between the calculated and experimental FT-IR and FT-Raman data indicates that the B3LYP/6-31G (d, p) can generate reliable geometry and related properties of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…The application of IR spectroscopy analysis as a preliminary analytical technique indicated the presence of the stated active ingredients for products 1 and 3. It also pointed to the presence of the active ingredient stanozolol in the unknown formulation of product 2 since this synthetic androgen had particular groups and distinct chemical transitions 25 . However, for the other samples, it was not possible to identify clear distinctions because testosterone and nandrolone esters as they differ only in the carbon length of their side chains.…”
Section: Discussionmentioning
confidence: 99%
“…The application of IR spectroscopy analysis as a preliminary analytical technique indicated the presence of the stated active ingredients for products 1 and 3. It also pointed to the presence of the active ingredient stanozolol in the unknown formulation of product 2 since this synthetic androgen had particular groups and distinct chemical transitions 25 . However, for the other samples, it was not possible to identify clear distinctions because testosterone and nandrolone esters as they differ only in the carbon length of their side chains.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, STZ also has a low water and salt retention (El Osta et al, 2016). The poor water solubility of STZ decreases its bioavailability, resulting in low efficacy, high inter-individual variability and, consequently, an unpredictable response (Lemma et al, 2017;Fasinu et al, 2011). To address these issues, herein, an innovative compound consisting of STZ conjugated with α-methoxy-ω-amino PEG having a nominal molecular weight (MW) of 10000 Da [(MeO-PEG-NH2)10kDa], (MeO-PEG-NH)10kDa-STZ, was synthesized.…”
Section: Systemic Administration Of Aass Is Providing Some Encouraginmentioning
confidence: 99%
“…bending, and 28 torsion internal coordinates, by including redundancies (Lemma et al, 2017), may be found in its relative IR spectrum (Fig. 3).…”
Section: 22) Due To the Physicochemical Property Of The Attachedmentioning
confidence: 99%
“…Gas chromatography coupled to mass spectrometry (MS) is widely used for screening, while liquid chromatography coupled to MS or tandem mass spectrometry (MS/MS) ensures the required analysis precision, specificity and sensibility with minimal sample pretreatment (18,19). Moreover, spectroscopic methods such as proton nuclear magnetic resonance (1H NMR), Raman and Fourier transform infrared spectroscopy (FT-IR) can be applied to the identification and quantitation of stanozolol (14,20). In addition, the use of high-resolution mass spectrometry (HRMS) methods is suggested due to the ability to improve mass accuracy and enhance the selectivity of the target compounds and/or allow for the analysis of untargeted compounds.…”
Section: Introductionmentioning
confidence: 99%